Atualização do módulo de reconhecimento de movimentos de um jogo terapêutico utilizando a biblioteca openpose - SILVA, Esther Cardoso da (2019)
Physical therapy is a process composed of repetitive tasks and, therefore, results in high rates of treatment quitting by the patients. Fitness games, also called exergames, offer a low-cost alternative to make this process more enjoyable. However, commercial exergames do not have the necessary exercise routines for the rehabilitation of patients with specific needs. Therefore, the development of serious games with activities designed for this context has been gaining great interest in the academic environment and the healthcare field. Skyway is a therapeutic game developed by Computer Engineering students at the Federal University of Pará, aimed at improving body balance for patients with locomotion problems. The motion tracking module of this exergame was developed with tools specific to the Microsoft Kinect device, Xbox console’s motion sensor, which uses color data, derived from RGB images, and depth data, obtained by infrared, to estimate the player’s position. Due to the Kinect device being pulled out from the market by the manufacturer in September 2017, it became desirable to replace it with a more modern tool. OpenPose is a free, open source library for non-commercial applications that uses image segmentation and machine learning techniques to recognize movements and expressions of people in 2D images. This tool was chosen to replace the Kinect development kit for being free of costs and for allowing the use of different kinds of imaging devices. After replacing the development kit, a comparison was made between the features present in both versions of the game. The game developed with the OpenPose library succeeded in moving the character on the horizontal axis, however, due to the limitations of three-dimensional coordinates in the Unity plugin, it was not possible to implement the character movement on the vertical axis. It has also been noted from limited testing that the game retains the performance of the original version only when library processing is done on CUDA-enabled graphics cards, but has proved impractical for execution only on the processors available for testing.